Optical coherence tomography in diabetic macular edema: sub-retinal fluid pattern and related risk factors - Gupta, Aditi; Raman, Rajiv; Sharma, Tarun (Nepalese Journal of Ophthalmology, 2014)
DOI: http://dx.doi.org/10.3126/nepjoph.v6i1.10786 Nepal J Ophthalmol 2014; 6 (2): 123-124